DETERMINANTS OF AUDIT QUALITY IN THE PUBLIK ACCOUNTING FIRM IN SEMARANG - mardaniaswari, attala; sukesti, fatmasari; fakhruddin, iwan; Roqijah, ifa (EconBank: Journal of Economics and Banking, 2023)
This study aims to find out and analyze the determinant factors that influence audit quaity, especially audit complexity, time budget pressure, and experience of auditors in empirical studies of publik Accounting Firms in Semarang. The accidental sampling technique obtained as many as 60 respondents with specific differences. The method in this study is quantitative, using the SmartPLS 4.0 test. The population of this research is all KAP auditors in Semarang. This study's results show that auditing complexity, time budget pressure, and auditor experience provide empirical evidence of a significant positive effect on audit quality. Suggestions for future researchers can add variations in variables, samples, and factors that support the influence of good audit quality.